(untitled) (Journal of Environmental Science and Natural Resources, 2012)
An experiment was carried out to study the effect of temperature on biology, oviposition and feeding behaviour as well as host preference of Epilachna beetle, Epilachna dodecastigma (Wied.) on eight varieties of brinjal, Solanum melongena Linn. from November, 2009 to June, 2010 maintaining controlled temperatures of 15ºC, 25ºC and 30ºC using an incubator in the Department of Entomology, BAU, Mymensingh. Temperature has a profound influence on the oviposition and food consumption of Epilachna beetle. In incubator at 15oC, 25oC and 30oC temperature, larval daily average food consumption (mm2) among eight host plant varieties of S. melongena was the highest on Thamba and the lowest on Bijoy, whereas adults daily mean food consumption at three temperature regimes was the highest on Thamba and the lowest on BAU-2 at 15oC and 25oC temperature and at 30oC temperature the lowest recorded on Bijoy. At 25oC temperature, the highest oviposition was recorded on Thamba and the lowest found on Jhumki. Similarly at 15oC and 30oC temperature, the highest oviposition was also observed on Thamba and the lowest on Bijoy. Thus, the varieties namely Thamba, ISD 006 and Kazla appeared to be preferable hosts, whereas Bijoy, BAU-2 and Jhumki seemed to less preferable. The results revealed that temperature had direct effect on the behaviour and 25°C temperature was congenial to both fecundity and food consumption of the Epilachna beetle. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11572 J. Environ. Sci. & Natural Resources, 5(1): 167 - 172, 2012